2021
DOI: 10.4269/ajtmh.20-1172
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors and Protective Immunity Against Rabies in Unvaccinated Butchers Working at Dog Slaughterhouses in Northern Vietnam

Abstract: Vietnam is a rabies-endemic country where eating dog meat is customary. However, the risks of rabies transmission to dog slaughtering and processing workers have not been identified. This study aimed to determine the rabies neutralizing antibody (NTA) and risk factors in dog slaughterers to propose appropriate intervention methods for this occupational group. In 2016, a cross-sectional study on NTA against rabies virus and related factors was conducted among 406 professional dog slaughterers in Vietnam. The pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Dog butchers in Vietnam were at high risk of rabies virus infection 31. The study found that 28.3% of butchers were at risk of rabies exposure due to the slaughtering of sick dogs and getting bites, scratches or knife cuts.…”
Section: Resultsmentioning
confidence: 95%
See 3 more Smart Citations
“…Dog butchers in Vietnam were at high risk of rabies virus infection 31. The study found that 28.3% of butchers were at risk of rabies exposure due to the slaughtering of sick dogs and getting bites, scratches or knife cuts.…”
Section: Resultsmentioning
confidence: 95%
“…Dog butchers in Vietnam were at high risk of rabies virus infection. 31 The study found that 28.3% of butchers were at risk of rabies exposure due to the slaughtering of sick dogs and getting bites, scratches or knife cuts. Of 406 participants, 8.6% had sufficient levels of rabies neutralising antibody for protection and only 8.1% were vaccinated.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The genetic characterization of rabies recovery from Burkino-Faso and Viet Nam demonstrated that the isolates exhibited similarities with those obtained from Mauritania and China, respectively (De Benedictis et al 2010;Nguyen et al 2011). Another example, dog slaughterhouses are considered as hotspot of rabies and dog butchers become at a high risk of rabies virus infection (Nguyen et al 2021). This suggests that rabies has the potential to spread across borders, underscoring the importance of dog trading and slaughtering in the epidemiology of rabies and warranting further concern.…”
Section: Introductionmentioning
confidence: 97%